Glass tempering process
By mixing molten salt and electric field-assisted process and coating liquid treatment, the existing tempered glass process solves the problems of long tempering time and easy adsorption of pollutants, achieves uniform tempering and high scratch resistance of the glass, and significantly improves its Aesthetics and light transmittance.
Patent Information
- Application Number
- CN202210446513.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-26
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-04-26
AI Technical Summary
The existing tempered glass process has problems such as long tempering time, uneven ion exchange depth, easy self-destruction, and easy adsorption of pollutants, which affects its aesthetics and light transmittance.
The glass is processed using a mixed molten salt and electric field-assisted process to evenly diffuse potassium ions and accelerate the ion exchange rate to improve the tempering effect. The scratch resistance and self-cleaning performance of the glass are enhanced through coating liquid spraying and annealing.
It achieves uniform tempering of the glass, improves its scratch resistance and self-cleaning performance, has super-hydrophobicity, and significantly improves the beauty and light transmittance of the glass.
Smart Images

Figure BDA0003617119400000131 
Figure BDA0003617119400000141 
Figure BDA0003617119400000142
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass processing, and in particular to a glass tempering process. Background Art
[0002] Glass is an amorphous inorganic non-metallic material. Its main components are silicon dioxide and other oxides. It is widely used in construction, industry and other fields because of its transparency and beauty. Ordinary glass is easy to break, has poor transparency, and is easy to absorb pollutants. In order to improve the strength of the glass, ordinary glass is usually tempered to improve its performance and expand its application range. Tempered glass is actually a prestressed glass. In order to improve the strength of the glass, chemical or physical methods are usually used to form compressive stress on the surface of the glass. When the glass is subjected to external force, the surface stress is first offset, thereby improving the bearing capacity and enhancing the glass's own resistance to wind pressure, cold and heat, and impact. With the rapid development of the glass industry, the demand for glass has gradually increased, but tempered glass also faces some problems, such as long tempering time, uneven ion exchange depth, easy self-explosion, easy adsorption of pollutants, and thus affecting the appearance and light transmittance.
[0003] Chinese patent CN108623140A discloses a molten salt and a tempering process for chemical tempering of ultra-thin soda-lime glass. The process mainly includes molten salt, which includes a main salt KNO 3 And a certain proportion of auxiliary salt Al 2 O 3 , K 2 CO 3 , KOH and CsNO 3 , achieving chemical tempering and strengthening of ultra-thin soda-lime glass, but did not improve the problems of uneven ion exchange depth, easy self-explosion, and easy adsorption of pollutants in tempered glass.
[0004] Therefore, the present invention discloses a super-hydrophobic and self-cleaning tempered glass and a glass tempering treatment process thereof. Summary of the invention
[0005] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide a glass tempering process.
[0006] A glass tempering process comprises the following steps:
[0007] S1 cuts, grinds, drills, and cleans flat glass with a thickness of 3-5 mm to obtain pre-treated flat glass, wherein the glass sheet has a size of (30-60) mm×(80-100) mm;
[0008] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 650-700° C. for 3-8 minutes;
[0009] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260-300° C.;
[0010] S4: soak the quenched flat glass in a mixed molten salt at 260-300°C in a DC electric field for 2-5 hours, cool to room temperature after the reaction, wash and dry, wherein the current density is 0.2-4 mA / cm 2 ;
[0011] S5: the flat glass cleaned and dried in step S4 is cleaned and dried to obtain tempered glass.
[0012] The mixed molten salt is composed of the following raw materials in parts by weight: 0.5-4 parts by weight of Nb 2 O 5 , 5-25 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 5-20 parts by weight of Al 2 O 3 , 30-50 parts by weight K 2 CO 3 , 1-5 parts by weight of potassium nitrate, 0.5-1 parts by weight of KMnO 4 , 0.5-2 parts by weight K 2 Cr 2 O 7 , 10-30 parts by weight of potassium lauryl phosphate.
[0013] The glass is immersed in mixed molten salt and assisted by electric field, which can not only make the potassium ions diffuse evenly, but also accelerate the ion exchange rate and improve the tempering effect; potassium salt of perfluoroalkyl ether carboxylic acid and potassium salt of dodecyl phosphate, Nb 2 O 5 The interaction forms a dense penetration layer, which makes the molecules in the glass bond more tightly, further improving the scratch resistance of tempered glass.
[0014] Furthermore, a glass tempering process comprises the following steps:
[0015] S1 cuts, grinds, drills, and cleans flat glass with a thickness of 3-5 mm to obtain pre-treated flat glass, wherein the glass sheet has a size of (30-60) mm×(80-100) mm;
[0016] S2: maintaining the flat glass pretreated in step S1 at a heating temperature of 650-700° C. for 3-8 minutes;
[0017] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260-300° C.;
[0018] S4: soak the quenched flat glass in a mixed molten salt at 260-300°C in a DC electric field for 2-5 hours, cool to room temperature after the reaction, wash and dry, wherein the current density is 0.2-4 mA / cm 2 ;
[0019] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.5-0.7 MPa, the spraying distance is 15-20 cm, and the thickness of the coating liquid is 12-18 μm;
[0020] S6: baking the flat glass after coating in step S5 at 200-230° C. for 35-50 minutes;
[0021] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0022] The coating solution is composed of the following raw materials in parts by weight: 5-15 parts by weight of titanium dioxide, 5-10 parts by weight of sepiolite, 0.5-5 parts by weight of ethyl orthosilicate, 0.5-2 parts by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2-3 parts by weight of potassium persulfate, and 70-80 parts by weight of water.
[0023] Further preferably, the plating solution is composed of the following raw materials in parts by weight: 5-15 parts by weight of titanium dioxide, 5-10 parts by weight of modified sepiolite, 0.5-5 parts by weight of tetraethyl orthosilicate, 0.5-2 parts by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2-3 parts by weight of potassium persulfate, and 70-80 parts by weight of water.
[0024] The preparation method of the modified sepiolite comprises the following steps:
[0025] (1) adding sepiolite and a coupling agent to water and subjecting to ultrasonic treatment for 30-60 min, wherein the ultrasonic power is 500-1000 W and the ultrasonic frequency is 18-24 kHz, then heating to 70-90° C. for reaction for 1-3 h, centrifuging to obtain a precipitate, washing, and drying to obtain a pretreated sepiolite, wherein the mass ratio of the sepiolite, the coupling agent, and the water is 1:(2-6):(15-25);
[0026] (2) adding the pretreated sepiolite prepared in step (1), silicotungstic acid aqueous solution, fluorine-containing organic matter, and allyl heptanoate to N,N-dimethylformamide, heating to 60-80°C for reaction for 40-60 minutes, then adding azobisisobutyl cyanide, maintaining the temperature at 60-80°C for reaction for 20-48 hours, washing with ether after the reaction, filtering out the precipitate, and drying to obtain modified sepiolite, wherein the mass ratio of the pretreated sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, allyl heptanoate, and N,N-dimethylformamide is 1:(10-15):(3-5):(0.1-0.5):(10-20), and the mass ratio of the pretreated sepiolite to azobisisobutyl cyanide is 1:(0.1-0.5).
[0027] The fluorine-containing organic compound is one of 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentane-2-yl methacrylate and 2,2,3,3,4,4,5,5,5-nonafluoromethyl methacrylate or a mixture of two thereof. Preferably, the fluorine-containing organic compound is a mixture of 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentane-2-yl methacrylate and 2,2,3,3,4,4,5,5,5-nonafluoromethyl methacrylate in a mass ratio of (1-3):(1-3).
[0028] The coupling agent is one or two or a mixture of two or more of vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tributanoximosilane, vinyl triacetoxysilane, γ-aminopropyl triethoxysilane, and N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane. Preferably, the coupling agent is a mixture of vinyl tributanoximosilane and N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane in a mass ratio of (1-3):(1-3).
[0029] The silicotungstic acid aqueous solution is obtained by mixing silicotungstic acid and water in a mass ratio of (0.1-0.5):(10-15).
[0030] Sepiolite is a porous inorganic material with pores running through the entire structure and a large specific surface area. Vinyl trisbutyl ketoxime silane and N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane are used to pretreat the sepiolite. The Si-OH ion groups in the coupling agent can interact with the molecules adsorbed on the outer surface of the sepiolite, giving the sepiolite an excellent self-cleaning effect. Then silicotungstic acid reacts with the active groups in the coupling agent and is grafted on the surface of the sepiolite, that is, the dispersion performance of silicotungstic acid is improved while improving its specific surface area, further improving its photocatalytic performance. At the same time, fluorine-containing organic matter and allyl heptanoate are added and grafted on the sepiolite under the action of the initiator to form a network structure. The introduction of silane and fluorine-containing monomers gives the tempered glass excellent superhydrophobic properties. 5,5,5-Trifluoro-4-hydroxy-4-(trifluoromethyl)pentan-2-yl methacrylate and 2,2,3,3,4,4,5,5,5-pentyl nonafluoromethacrylate were synergistically grafted onto sepiolite, which can further improve the surface hydrophobicity due to the low surface energy of long-chain fluorinated organic compounds.
[0031] The synergistic effect of titanium dioxide and modified sepiolite further improves the photocatalytic performance. Titanium dioxide, modified sepiolite, ethyl orthosilicate, surfactants and water interact to form a dense structure, which makes the coating solution have good stability.
[0032] After being treated with mixed molten salt, the glass is further tempered to soften the glass surface, reorganize the structure, increase the roughness of the glass surface, increase the specific surface area of contact between the coating liquid and the glass and its bonding force, and after secondary annealing treatment, further improve the self-cleaning performance of the glass surface.
[0033] Beneficial effects of the invention: The invention discloses a glass tempering process, which uses a mixed molten salt and electric field-assisted method to treat the glass, which can not only make potassium ions diffuse evenly, but also accelerate the ion exchange rate, improve the tempering effect, and make the molecules in the glass more tightly bound, further improving the scratch resistance of the tempered glass. The tempered glass prepared by the invention has lotus leaf super-hydrophobicity and self-cleaning properties. At the same time, the method of the invention is simple, low-cost, and has good economic benefits. DETAILED DESCRIPTION
[0034] Raw materials used in this experiment:
[0035] The flat glass in the embodiment is ordinary soda-lime silicate float glass, the main component of which is 72.8% SiO 2 、13.86%Na 2 O, 8.61% CaO, 3.42% MgO, 0.84% Al 2 O 3 , 0.12%K 2 O, 0.35% others.
[0036] Nb 2 O 5 , particle size: 7-10um, purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0037] Al 2 O 3 , particle size: 1um, Yuejiang New Materials (Guangzhou) Co., Ltd.
[0038] The sepiolite in the embodiment is sepiolite powder with a particle size of 200 mesh, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0039] The perfluoroalkyl ether carboxylic acid potassium salt in the embodiment is perfluoroalkyl ether carboxylic acid potassium salt FC-5, with a molecular formula of C 15 F 29 O 6 K was purchased from Shanghai Citailong Industrial Co., Ltd.
[0040] Potassium dodecyl phosphate, CAS: 39322-78-6.
[0041] The titanium dioxide in the embodiment is anatase phase, particle size: 20 nm, model: VK-TA18, purchased from Xuancheng Jingrui New Materials Co., Ltd.
[0042] Sodium dodecyl alcohol polyoxyethylene ether sulfate, CAS: 9004-82-4, viscosity: 100 MPa·s, was purchased from Hubei Hengjingrui Chemical Co., Ltd.
[0043] 5,5,5-Trifluoro-4-hydroxy-4-(trifluoromethyl)pentan-2-yl methacrylate, CAS: 630414-85-6.
[0044] 2,2,3,3,4,4,5,5,5-Nonafluoropentyl methacrylate, CAS: 59006-65-4.
[0045] Vinyltributylacetoximosilane, CAS: 2224-33-1.
[0046] N-β-(Aminoethyl)-γ-aminopropyltrimethoxysilane, CAS: 1760-24-3.
[0047] Example 1
[0048] A glass tempering process comprises the following steps: S1 cutting, grinding, drilling and cleaning a flat glass with a thickness of 5 mm to obtain a pre-treated flat glass, wherein the glass sheet has a size of 60 mm×100 mm;
[0049] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 660° C. for 5 minutes;
[0050] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2, so that the glass is evenly cooled to 260° C.;
[0051] S4: Soak the quenched flat glass in a 260°C mixed molten salt in a DC electric field for 4 hours, cool to room temperature after the reaction, wash and dry, with a current density of 1 mA / cm 2 ;
[0052] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.6 MPa, the spraying distance is 18 cm, and the thickness of the coating liquid is 12 μm;
[0053] S6: baking the flat glass after coating in step S5 at 230° C. for 40 minutes;
[0054] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0055] The mixed molten salt is composed of the following raw materials by weight: 2 parts by weight of Nb 2 O 5 22 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 11 parts by weight of Al 2 O 3 , 35 parts by weight K 2 CO 3 , 2 parts by weight of potassium nitrate, 0.5 parts by weight of KMnO 4 , 1 part by weight K 2 Cr 2 O 7 , 25 parts by weight of potassium lauryl phosphate.
[0056] The coating solution is composed of the following raw materials in parts by weight: 8 parts by weight of titanium dioxide, 10 parts by weight of sepiolite, 3 parts by weight of ethyl orthosilicate, 1 part by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2 parts by weight of potassium persulfate, and 70 parts by weight of water.
[0057] Example 2
[0058] A glass tempering process comprises the following steps:
[0059] S1 cuts, grinds, drills and cleans the flat glass with a thickness of 5 mm to obtain pre-treated flat glass with a size of 60 mm × 100 mm;
[0060] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 660° C. for 5 minutes;
[0061] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260° C.;
[0062] S4: Soak the quenched flat glass in a 260°C mixed molten salt in a DC electric field for 4 hours, cool to room temperature after the reaction, wash and dry, with a current density of 1 mA / cm 2 ;
[0063] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.6 MPa, the spraying distance is 18 cm, and the thickness of the coating liquid is 12 μm;
[0064] S6: baking the flat glass after coating in step S5 at 230° C. for 40 minutes;
[0065] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0066] The mixed molten salt is composed of the following raw materials by weight: 2 parts by weight of Nb 2 O 5 , 22 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 11 parts by weight of Al 2 O 3 , 35 parts by weight K 2 CO 3 , 2 parts by weight of potassium nitrate, 0.5 parts by weight of KMnO 4 , 1 part by weight K 2 Cr 2 O 7 , 25 parts by weight of potassium lauryl phosphate.
[0067] The coating solution is composed of the following raw materials in parts by weight: 8 parts by weight of titanium dioxide, 10 parts by weight of modified sepiolite, 3 parts by weight of ethyl orthosilicate, 1 part by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2 parts by weight of potassium persulfate, and 70 parts by weight of water.
[0068] The preparation method of the modified sepiolite comprises the following steps:
[0069] (1) adding sepiolite and a coupling agent to water and subjecting to ultrasonic treatment for 30 minutes, wherein the ultrasonic power is 600 W and the ultrasonic frequency is 20 kHz, then heating to 85° C. for reaction for 2 hours, centrifuging to obtain a precipitate, washing with water, and drying to obtain a pretreated sepiolite, wherein the mass ratio of the sepiolite, the coupling agent, and water is 1:4:15;
[0070] (2) adding the pretreated sepiolite prepared in step (1), silicotungstic acid aqueous solution, fluorine-containing organic matter, and allyl heptanoate to N,N-dimethylformamide, heating to 70° C. for reaction for 60 min, then adding azobisisobutyl cyanide, maintaining the temperature at 70° C. for reaction for 32 h, washing with ether after the reaction, filtering out the precipitate, and drying to obtain modified sepiolite, wherein the mass ratio of the pretreated sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, allyl heptanoate, and N,N-dimethylformamide is 1:10:4:0.5:15, and the mass ratio of the pretreated sepiolite and azobisisobutyl cyanide is 1:0.5.
[0071] The fluorine-containing organic compound is a mixture of 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentan-2-yl methacrylate and 2,2,3,3,4,4,5,5,5-nonafluoropentyl methacrylate in a mass ratio of 2:3.
[0072] The coupling agent is a mixture of vinyl tributylidene oxime silane and N-β-(aminoethyl)-γ-aminopropyl trimethoxy silane in a mass ratio of 1:1.
[0073] The silicotungstic acid aqueous solution is obtained by mixing silicotungstic acid and water in a mass ratio of 0.5:15.
[0074] Example 3
[0075] A glass tempering process comprises the following steps: S1 cutting, grinding, drilling and cleaning a flat glass with a thickness of 5 mm to obtain a pre-treated flat glass with a size of 60 mm×100 mm;
[0076] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 660° C. for 5 minutes;
[0077] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260° C.;
[0078] S4: Soak the quenched flat glass in a 260°C mixed molten salt in a DC electric field for 4 hours, cool to room temperature after the reaction, wash and dry, with a current density of 1 mA / cm 2 ;
[0079] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.6 MPa, the spraying distance is 18 cm, and the thickness of the coating liquid is 12 μm;
[0080] S6: baking the flat glass after coating in step S5 at 230° C. for 40 minutes;
[0081] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0082] The mixed molten salt is composed of the following raw materials by weight: 2 parts by weight of Nb 2 O 5 , 22 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 11 parts by weight of Al 2 O 3 , 35 parts by weight K 2 CO 3 , 2 parts by weight of potassium nitrate, 0.5 parts by weight of KMnO 4 , 1 part by weight K 2 Cr 2 O 7 , 25 parts by weight of potassium lauryl phosphate.
[0083] The coating solution is composed of the following raw materials in parts by weight: 8 parts by weight of titanium dioxide, 10 parts by weight of modified sepiolite, 3 parts by weight of ethyl orthosilicate, 1 part by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2 parts by weight of potassium persulfate, and 70 parts by weight of water.
[0084] The preparation method of the modified sepiolite comprises the following steps:
[0085] (1) adding sepiolite and a coupling agent to water and subjecting to ultrasonic treatment for 30 minutes, wherein the ultrasonic power is 600 W and the ultrasonic frequency is 20 kHz, then heating to 85° C. for reaction for 2 hours, centrifuging to obtain a precipitate, washing with water, and drying to obtain a pretreated sepiolite, wherein the mass ratio of the sepiolite, the coupling agent, and water is 1:4:15;
[0086] (2) adding the pretreated sepiolite prepared in step (1), silicotungstic acid aqueous solution, fluorine-containing organic matter, and allyl heptanoate to N,N-dimethylformamide, heating to 70° C. for reaction for 60 min, then adding azobisisobutyl cyanide, maintaining the temperature at 70° C. for reaction for 32 h, washing with ether after the reaction, filtering out the precipitate, and drying to obtain modified sepiolite, wherein the mass ratio of the pretreated sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, allyl heptanoate, and N,N-dimethylformamide is 1:10:4:0.5:15, and the mass ratio of the pretreated sepiolite and azobisisobutyl cyanide is 1:0.5.
[0087] The fluorine-containing organic compound is 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentane-2-yl methacrylate.
[0088] The coupling agent is a mixture of vinyl tributylidene oxime silane and N-β-(aminoethyl)-γ-aminopropyl trimethoxy silane in a mass ratio of 1:1.
[0089] The silicotungstic acid aqueous solution is obtained by mixing silicotungstic acid and water in a mass ratio of 0.5:15.
[0090] Example 4
[0091] A glass tempering process comprises the following steps: S1 cutting, grinding, drilling and cleaning a flat glass with a thickness of 5 mm to obtain a pre-treated flat glass with a size of 60 mm×100 mm;
[0092] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 660° C. for 5 minutes;
[0093] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260° C.;
[0094] S4: Soak the quenched flat glass in a 260°C mixed molten salt in a DC electric field for 4 hours, cool to room temperature after the reaction, wash and dry, with a current density of 1 mA / cm 2 ;
[0095] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.6 MPa, the spraying distance is 18 cm, and the thickness of the coating liquid is 12 μm;
[0096] S6: baking the flat glass after coating in step S5 at 230° C. for 40 minutes;
[0097] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0098] The mixed molten salt is composed of the following raw materials by weight: 2 parts by weight of Nb 2 O 5 , 22 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 11 parts by weight of Al 2 O 3 , 35 parts by weight K 2 CO 3 , 2 parts by weight of potassium nitrate, 0.5 parts by weight of KMnO 4 , 1 part by weight K 2 Cr 2 O 7 , 25 parts by weight of potassium lauryl phosphate.
[0099] The coating solution is composed of the following raw materials in parts by weight: 8 parts by weight of titanium dioxide, 10 parts by weight of modified sepiolite, 3 parts by weight of ethyl orthosilicate, 1 part by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2 parts by weight of potassium persulfate, and 70 parts by weight of water.
[0100] The preparation method of the modified sepiolite comprises the following steps:
[0101] (1) adding sepiolite and a coupling agent to water and subjecting to ultrasonic treatment for 30 minutes, wherein the ultrasonic power is 600 W and the ultrasonic frequency is 20 kHz, then heating to 85° C. for reaction for 2 hours, centrifuging to obtain a precipitate, washing with water, and drying to obtain a pretreated sepiolite, wherein the mass ratio of the sepiolite, the coupling agent, and water is 1:4:15;
[0102] (2) adding the pretreated sepiolite prepared in step (1), silicotungstic acid aqueous solution, fluorine-containing organic matter, and allyl heptanoate to N,N-dimethylformamide, heating to 70° C. for reaction for 60 min, then adding azobisisobutyl cyanide, maintaining the temperature at 70° C. for reaction for 32 h, washing with ether after the reaction, filtering out the precipitate, and drying to obtain modified sepiolite, wherein the mass ratio of the pretreated sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, allyl heptanoate, and N,N-dimethylformamide is 1:10:4:0.5:15, and the mass ratio of the pretreated sepiolite and azobisisobutyl cyanide is 1:0.5.
[0103] The fluorine-containing organic compound is 2,2,3,3,4,4,5,5,5-nonafluoropentyl methylacrylate.
[0104] The coupling agent is a mixture of vinyl tributylidene oxime silane and N-β-(aminoethyl)-γ-aminopropyl trimethoxy silane in a mass ratio of 1:1.
[0105] The silicotungstic acid aqueous solution is obtained by mixing silicotungstic acid and water in a mass ratio of 0.5:15.
[0106] Example 5
[0107] A glass tempering process comprises the following steps: S1 cutting, grinding, drilling and cleaning a flat glass with a thickness of 5 mm to obtain a pre-treated flat glass with a size of 60 mm×100 mm;
[0108] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 660° C. for 5 minutes;
[0109] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260° C.;
[0110] S4: Soak the quenched flat glass in a 260°C mixed molten salt in a DC electric field for 4 hours, cool to room temperature after the reaction, wash and dry, with a current density of 1 mA / cm 2 ;
[0111] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.6 MPa, the spraying distance is 18 cm, and the thickness of the coating liquid is 12 μm;
[0112] S6: baking the flat glass after coating in step S5 at 230° C. for 40 minutes;
[0113] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0114] The mixed molten salt is composed of the following raw materials by weight: 2 parts by weight of Nb 2 O 5 , 22 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 11 parts by weight of Al 2 O 3 , 35 parts by weight K 2 CO 3 , 2 parts by weight of potassium nitrate, 0.5 parts by weight of KMnO 4 , 1 part by weight K 2 Cr 2 O 7 , 25 parts by weight of potassium lauryl phosphate.
[0115] The coating solution is composed of the following raw materials in parts by weight: 8 parts by weight of titanium dioxide, 10 parts by weight of modified sepiolite, 3 parts by weight of ethyl orthosilicate, 1 part by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2 parts by weight of potassium persulfate, and 70 parts by weight of water.
[0116] The preparation method of the modified sepiolite comprises the following steps:
[0117] (1) adding sepiolite and a coupling agent to water and subjecting to ultrasonic treatment for 30 minutes, wherein the ultrasonic power is 600 W and the ultrasonic frequency is 20 kHz, then heating to 85° C. for reaction for 2 hours, centrifuging to obtain a precipitate, washing with water, and drying to obtain a pretreated sepiolite, wherein the mass ratio of the sepiolite, the coupling agent, and water is 1:4:15;
[0118] (2) adding the pretreated sepiolite, fluorinated organic matter and allyl heptanoate prepared in step (1) to N,N-dimethylformamide, heating to 70°C and reacting for 60 minutes, then adding azobisisobutyl cyanide, maintaining the temperature at 70°C and reacting for 32 hours, washing with ether after the reaction, filtering and drying the precipitate to obtain modified sepiolite, wherein the mass ratio of the pretreated sepiolite, fluorinated organic matter, allyl heptanoate and N,N-dimethylformamide is 1:4:0.5:15, and the mass ratio of the pretreated sepiolite and azobisisobutyl cyanide is 1:0.5.
[0119] The fluorine-containing organic compound is 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentane-2-yl methacrylate.
[0120] The coupling agent is a mixture of vinyl tributylidene oxime silane and N-β-(aminoethyl)-γ-aminopropyl trimethoxy silane in a mass ratio of 1:1.
[0121] Example 6
[0122] A glass tempering process comprises the following steps: S1 cutting, grinding, drilling and cleaning a flat glass with a thickness of 5 mm to obtain a pre-treated flat glass with a size of 60 mm×100 mm;
[0123] S2: maintaining the pretreated flat glass in step S1 at a heating temperature of 660° C. for 5 minutes;
[0124] S3 performs low-temperature high-speed ventilation and quenching on both sides of the flat glass heated in step S2 to cool the glass to 260° C.;
[0125] S4: Soak the quenched flat glass in a 260°C mixed molten salt in a DC electric field for 4 hours, cool to room temperature after the reaction, wash and dry, with a current density of 1 mA / cm 2 ;
[0126] S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.6 MPa, the spraying distance is 18 cm, and the thickness of the coating liquid is 12 μm;
[0127] S6: baking the flat glass after coating in step S5 at 230° C. for 40 minutes;
[0128] S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass.
[0129] The mixed molten salt is composed of the following raw materials by weight: 2 parts by weight of Nb 2 O 5 , 22 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 11 parts by weight of Al 2 O 3 , 35 parts by weight K 2 CO 3 , 2 parts by weight of potassium nitrate, 0.5 parts by weight of KMnO 4 , 1 part by weight K 2 Cr 2 O 7 , 25 parts by weight of potassium lauryl phosphate.
[0130] The coating solution is composed of the following raw materials in parts by weight: 8 parts by weight of titanium dioxide, 10 parts by weight of modified sepiolite, 3 parts by weight of ethyl orthosilicate, 1 part by weight of sodium dodecyl alcohol polyoxyethylene ether sulfate, 2 parts by weight of potassium persulfate, and 70 parts by weight of water.
[0131] The preparation method of the modified sepiolite comprises the following steps:
[0132] Add sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, and allyl heptanoate to N,N-dimethylformamide, heat to 70°C and react for 60 minutes, then add azobisisobutyl cyanide, keep the temperature at 70°C and react for 32 hours, wash with ether after the reaction, filter out the precipitate, and dry to obtain modified sepiolite, wherein the mass ratio of the sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, allyl heptanoate, and N,N-dimethylformamide is 1:10:4:0.5:15, and the mass ratio of the pretreated sepiolite and azobisisobutyl cyanide is 1:0.5.
[0133] The fluorine-containing organic compound is 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentane-2-yl methacrylate.
[0134] The silicotungstic acid aqueous solution is obtained by mixing silicotungstic acid and water in a mass ratio of 0.5:15.
[0135] Test Example 1
[0136] (1) Adhesion test: Adhesion test was performed on the tempered glass prepared in Examples 1 to 6 with reference to GB / T9286-1998 “Scratch test for paint and varnish films”.
[0137] Table 1 Test results of toughened glass adhesion
[0138]
[0139]
[0140] (2) Test of contact angle θ: A Chengde Dingsheng JY-82 contact angle meter was used, and the arithmetic mean of ten test values was taken.
[0141] Table 2 Test results of tempered glass contact angle
[0142] Contact angle (°) Example 1 157 Example 2 171 Example 3 166 Example 4 168 Example 5 161 Example 6 162
[0143] By comparing Examples 2-4, it is found that the super hydrophobicity of Example 2 is significantly better than that of Examples 3-4. The possible reason is that 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentane-2-yl methacrylate and 2,2,3,3,4,4,5,5,5-nonafluoromethylacrylate are synergistically grafted on sepiolite, and the surface hydrophobicity can be further improved due to the low surface energy of long-chain fluorinated organic matter.
[0144] Test Example 2
[0145] Photocatalytic test: Take 3 mL of rhodamine B / ethanol solution (3.0×10 -4 mol / L) was evenly dripped onto the tempered glass prepared in Example 1-6, and the color value (L1 、a 1 , b 1 ), then put the tempered glass coated with Rhodamine B / ethanol solution into a dark box equipped with a daylight xenon lamp (power 300W) (the distance between the lamp and the coating surface is 10cm), turn on the xenon lamp light source, and measure the color value every 2min until the tempered glass coated with Rhodamine B / ethanol solution basically restores its own color (L 2 、a 2 , b 2 ) Calculate the change in color value ΔE after the photocatalytic test and before the photocatalytic test, where ΔE = [ΔL 2 +Δa 2 +Δb 2 ] 1 / 2 .
[0146] Table 3 Test results of tempered glass photocatalysis
[0147]
[0148]
[0149] By comparing Example 2 with Example 5, it is found that the photocatalytic performance of Example 2 is significantly better than that of Example 5. The possible reason is that the sepiolite is pretreated with vinyl trisbutyl ketoxime silane and N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane, and the Si-OH ion groups in the coupling agent can interact with the molecules adsorbed on the outer surface of the sepiolite, giving the sepiolite an excellent cleaning effect. Then the silicotungstic acid reacts with the active groups in the coupling agent and is grafted on the surface of the sepiolite, that is, the dispersion performance of the silicotungstic acid is improved while improving its specific surface area, further improving its photocatalytic performance.
Claims
1. Glass tempering process, characterized by: The following steps are involved: S1 cuts, grinds, drills, and cleans the flat glass to obtain pre-treated flat glass; S2: maintaining the pre-treated flat glass in step S1 at a heating temperature of 650-700° C. for 3-8 minutes; S3: low-temperature, high-speed and uniform ventilation is performed on both sides of the flat glass heated in step S2 to uniformly quench the glass, so that the glass is uniformly cooled to 260-300° C.; S4: soak the quenched flat glass in a mixed molten salt at 260-300°C in a DC electric field for 2-5 hours, cool to room temperature after the reaction, wash and dry, wherein the current density is 0.2-4 mA / cm 2 ; S5: spray coating the flat glass cleaned and dried in step S4 with a coating liquid, wherein the air pressure of the spraying is 0.5-0.7 MPa, the spraying distance is 15-20 cm, and the thickness of the coating liquid is 12-18 μm; S6: baking the flat glass after coating in step S5 at 200-230° C. for 35-50 minutes; S7: cleaning and drying the flat glass baked in step S6 to obtain tempered glass; The coating solution is composed of the following raw materials in parts by weight: 5-15 parts by weight of titanium dioxide, 5-10 parts by weight of modified sepiolite, 0.5-5 parts by weight of ethyl orthosilicate, 0.5-2 parts by weight of sodium lauryl alcohol polyoxyethylene ether sulfate, 2-3 parts by weight of potassium persulfate, and 70-80 parts by weight of water; The preparation method of the modified sepiolite, The following steps are involved: (1) adding sepiolite and a coupling agent to water and subjecting to ultrasonic treatment for 30-60 min, wherein the ultrasonic power is 500-1000 W and the ultrasonic frequency is 18-24 kHz, then heating to 70-90° C. for reaction for 1-3 h, centrifuging to obtain a precipitate, washing, and drying to obtain a pretreated sepiolite, wherein the mass ratio of the sepiolite, the coupling agent, and the water is 1:(2-6):(15-25); (2) adding the pretreated sepiolite prepared in step (1), silicotungstic acid aqueous solution, fluorine-containing organic matter, and allyl heptanoate to N,N-dimethylformamide, heating to 60-80°C for reaction for 40-60 minutes, then adding azobisisobutyl cyanide, maintaining the temperature at 60-80°C for reaction for 20-48 hours, washing with ether after the reaction, filtering out the precipitate, and drying to obtain modified sepiolite, wherein the mass ratio of the pretreated sepiolite, silicotungstic acid aqueous solution, fluorine-containing organic matter, allyl heptanoate, and N,N-dimethylformamide is 1:(10-15):(3-5):(0.1-0.5):(10-20), and the mass ratio of the pretreated sepiolite to azobisisobutyl cyanide is 1:(0.1-0.5).
2. The glass tempering process according to claim 1, characterized in that: The mixed molten salt is composed of the following raw materials in parts by weight: 0.5-4 parts by weight of Nb2O5, 5-25 parts by weight of perfluoroalkyl ether carboxylic acid potassium salt, 5-20 parts by weight of Al2O3, 30-50 parts by weight of K2CO3, 1-5 parts by weight of potassium nitrate, 0.5-1 parts by weight of KMnO4, 0.5-2 parts by weight of K2Cr2O7, and 10-30 parts by weight of dodecyl phosphate potassium salt.
3. The glass tempering process according to claim 1, characterized in that: The fluorine-containing organic compound is a mixture of 5,5,5-trifluoro-4-hydroxy-4-(trifluoromethyl)pentan-2-yl methacrylate and 2,2,3,3,4,4,5,5,5-nonafluoropentyl methacrylate in a mass ratio of (1-3):(1-3).
4. The glass tempering process according to claim 1, characterized in that: The coupling agent is one or two or a mixture of two or more of vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tributanoximosilane, vinyl triacetoxysilane, γ-aminopropyl triethoxysilane and N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane.
5. A tempered glass, characterized in that: The glass is prepared by the glass tempering process as described in any one of claims 1 to 4.
Citation Information
Patent Citations
Molten salt for chemical tempering of ultrathin soda-lime glass and tempering process of molten salt
CN108623140A
Preparation method of self-cleaning toughened glass
CN104193184A
Preparation technology of tempered glass
CN109678329A
Tempered glass and preparation method thereof
CN114751656A
Novel fire-proof safety glass for building
CN1491911A